2022
DOI: 10.3390/ma15072534
|View full text |Cite
|
Sign up to set email alerts
|

Low-Friction of ta-C Coatings Paired with Brass and Other Materials under Vacuum and Atmospheric Conditions

Abstract: Vacuum environments provide challenging conditions for tribological systems. MoS2 is one of the materials commonly known to provide low friction for both ambient and vacuum conditions. However, it also exhibits poor wear resistance and low ability to withstand higher contact pressures. In search of wear-resistant alternatives, superhard hydrogen-free tetrahedral amorphous carbon coatings (ta-C) are explored in this study. Although known to have excellent friction and wear properties in ambient atmospheres, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although pure tetrahedral amorphous carbon (ta-C) coatings commonly have high friction and wear in a vacuum and cannot passivate as in air due to the absence of water, some notable exceptions have been reported. Härtwig et al studied the influence of different counter body materials when sliding against ta-C in a vacuum and found that a brass counter body resulted in unexpectedly low friction and wear [21]. A simple bilayer coating approach of MoS 2 on top of a ta-C coating deposited via vacuum arc deposition was found to improve the wear life in humid and vacuum conditions compared to a pure MoS 2 coating due to the underlaying hard ta-C coating [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although pure tetrahedral amorphous carbon (ta-C) coatings commonly have high friction and wear in a vacuum and cannot passivate as in air due to the absence of water, some notable exceptions have been reported. Härtwig et al studied the influence of different counter body materials when sliding against ta-C in a vacuum and found that a brass counter body resulted in unexpectedly low friction and wear [21]. A simple bilayer coating approach of MoS 2 on top of a ta-C coating deposited via vacuum arc deposition was found to improve the wear life in humid and vacuum conditions compared to a pure MoS 2 coating due to the underlaying hard ta-C coating [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are exceptions to this depending on the counter body material. In the case of a brass counter body to a ta-C coating, it has been shown that low friction and wear can be achieved in vacuum [23].…”
Section: Introductionmentioning
confidence: 99%